Mobile Device Data for Parks and Public Lands Transportation Planning: A Framework for Evaluation and Applications. Issue 8 (August 2022) - Baird, Timothy; Stinger, Preston; Cole, Erica; Collins, Rachel
Examination of mobile device data in transportation research and planning practices has occurred in a variety of contexts. However, little investigation of its potential to enhance transportation planning processes in parks and public lands has happened to date. The National Park Service partnered with the U.S. Department of Transportation Volpe Center and Colorado Department of Transportation to investigate how mobile device data can enhance regional and park-level transportation planning efforts by better answering questions about transportation system usage patterns. Using the StreetLight Insight data platform, we evaluated desired use cases and communication strategies for scoping, evaluating, procuring, and applying mobile device data to park- and system-level planning challenges. The analyses of a Colorado statewide visitor data sample were found to be promising data sources for planning tasks including understanding the relationships between gateway communities and parks, internal traffic/visitor flows, dwell times at internal park destinations, and speeds on park- and park-adjacent roadways.